Zonas de Kramer y medición de bilirrubina sérica en correlación con la medición de bilirrubina transcutánea en recién nacidos con ictericia neonatal - Utreras Figueroa, Bryan Jason (2021)
Jaundice is the yellowing of the skin in relation to hyperbilirubinemia, at least 60% of healthy newborns present it. It is almost always a non-serious health problem, however, its complications must be considered, particularly neurotoxicity. The characteristics of this pathology motivated this quantitative, analytical, correlation and cross-sectional study, which main purpose was to correlate Kramer's zones and serum bilirubin measurement with transcutaneous bilirubin measurement in 64 neonates diagnosed with neonatal jaundice. Obtaining as results: jaundice with a higher prevalence in the gestational age group of 39 weeks with 43.75% (n = 28), predominantly the female sex with 51.6% (n = 33). The anthropometric variables included their frequency according to the means of values, thus jaundice is related to: Weight: 3398.4 gr; Size: 50.2 cm; Head circumference: 34.27 cm; Thoracic circumference: 34.17 cm. The Pearson correlation index between Kramer's zones and transcutaneous bilirubin was 0.81 and serum bilirubin with transcutaneous bilirubin was 0.85. It is concluded that the bilirubin value measured transcutaneously is highly comparable to total serum bilirubin and Kramer's zones, since due to its high sensitivity it is useful as a non-invasive, low-cost and easy-to-apply hyperbilirubinemia screening method. However, it could not be used as a confirmatory test of disease. Key words: complications, screening, newborn.